The Role of Expert Opinions at the Investigation Stage in Efforts to Uncover Illegal Gold Mining Crimes Based on Article 120 of the Criminal Procedure Code in West Kalimantan - Susi Turti; Adi Nur Rahman (International Journal of Law, Crime and Justice, 2025)
This study examines the critical role of expert opinions from the Ministry of Energy and Mineral Resources (ESDM) during the investigation phase in uncovering gold mining without permit (PETI) crimes under Article 120 of the Indonesian Criminal Procedure Code (KUHAP) in West Kalimantan. The research employs a normative-empirical approach, analyzing legal provisions, government reports, and judicial practices to assess how ESDM experts contribute to establishing the material truth of PETI cases. Findings reveal that expert opinions are indispensable for verifying the absence of permits, assessing environmental damage, and quantifying state losses, thereby strengthening evidentiary frameworks for prosecutors and judges. However, challenges persist, including coordination gaps between law enforcement and ESDM, insufficient technical capacity among investigators, and potential threats to expert independence. The study concludes that optimizing the use of ESDM expertise is not merely procedural but strategic for effective, accountable, and just enforcement against PETI, which remains a significant threat to national resource sovereignty and environmental sustainability.